Skills for Digitalization: Employer Strategies for Competence Management in Manufacturing - Davidsson, Anna; Røed Steen, Johan (Nordic Journal of Working Life Studies, 2026)
Digitalization and the transition toward Industry 4.0 in manufacturing involve changing organizational needs for skills and competences, which, in turn, necessitate strategies for digital competence management. Based on qualitative interviews in four manufacturing companies in Norway and Sweden, this study shows how the transition to digitalized production involves several key decisions regarding staffing strategies, job design, and competence development. Moreover, it illustrates how various contextual conditions influence these decisions. Recognizing these strategic choices as partly interdependent, two contrasting paths are presented: the enabling path vs. the pragmatic flexibility path. While institutional factors in Sweden and Norway mainly push toward the enabling path, company-specific factors push instead toward the pragmatic flexibility path.